2018
DOI: 10.4049/jimmunol.1800671
|View full text |Cite
|
Sign up to set email alerts
|

Influenza A Virus Infection Causes Chronic Lung Disease Linked to Sites of Active Viral RNA Remnants

Abstract: Clinical and experimental observations suggest that chronic lung disease is linked to respiratory viral infection. However, the long-term aspect of this relationship is not yet defined using a virus that replicates at properly high levels in humans and a corresponding animal model. In this study, we show that influenza A virus infection achieves 1 × 10-fold increases in viral load in the lung and dose-dependent severity of acute illness in mice. Moreover, these events are followed by persistence of negative- a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
105
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 77 publications
(121 citation statements)
references
References 96 publications
(109 reference statements)
11
105
0
2
Order By: Relevance
“…The clearance of infectious virus also raises the issue of persistent viral-RNA remnants that are likely noninfectious but might still have a role in postviral disease. In that context, we reported (and confirm in this study) that viral-RNA remnants are found long after clearance of infectious virus in the case of SeV (28), and we found the same persistence more recently for IAV (31). In addition, our report for IAV includes data for active viral-RNA replication with detection of both positive-and negative-strand viral RNA and for localization of these viral-RNA remnants to sites of chronic lung disease.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…The clearance of infectious virus also raises the issue of persistent viral-RNA remnants that are likely noninfectious but might still have a role in postviral disease. In that context, we reported (and confirm in this study) that viral-RNA remnants are found long after clearance of infectious virus in the case of SeV (28), and we found the same persistence more recently for IAV (31). In addition, our report for IAV includes data for active viral-RNA replication with detection of both positive-and negative-strand viral RNA and for localization of these viral-RNA remnants to sites of chronic lung disease.…”
Section: Discussionsupporting
confidence: 88%
“…9A). We detected no significant increase in baseline R RS at 8 or 49 d after viral infection in wild-type, Stat1 2/2 , or Foxj1-Scgb1a1-Cre-Stat1 f/f mice (data not shown), consistent with our studies of SeV and IAV infections (28,29,31). To further address the comparison between the post-EV-D68 mouse model with chronic lung disease in humans, we also assessed the development of fibrosis as a feature of airway disease.…”
Section: Epithelial Stat1 Function Protects Against Ev-d68-induced Chsupporting
confidence: 90%
See 2 more Smart Citations
“…This is supported by substantial evidence, much of it derived from animal models of experimental infection, that influenza virus infection is associated with alterations in the host respiratory tract that predispose to adherence, invasion and induction of disease by the pneumococcus [46]. These result in increased adhesion of the pneumococcus to virus-activated respiratory epithelium, together with alterations in pulmonary innate and adaptive immune responses that result in impaired clearance of the bacteria, as well as a chronic inflammatory response lasting for up to 26 weeks due to persistent viral antigenaemia, specifically RNA, in the lower airways [47][48][49]. Pneumococcal replication in the airways may be further enhanced by an increased availability of free sialic acids derived from cleavage of host mucin by viral neuraminidase [50].…”
Section: Cap Due To Influenza Virus Infectionmentioning
confidence: 99%